The development of virtual product life cycle design tool using artificial intelligence technique - Harun, Habibollah (Faculty of Computer Science and Information System, 2008)
In order to achieve the automated detection of features and the machining parameter, an understanding of how the manufacturing information can be obtained directly from the CAD system must be addressed. The integration of CAD/CAM through a database can be used as basis in obtaining geometry information for features and machining parameter. The most basic role of CAD is to define the geometry of the design which is essential to all the subsequent activities in the process planning. The common structure of the databases is recognizing through the logics, binary, comparisons, etc and sometimes difficult to interpret or make necessary change in the database. By not considering curve object, the considered features are hole, pocket, step and slot. This project presents the future works of an algorithm to classify features of DXF file and algorithm for mapping the features with machining parameter. The code is recognizing line by line to classify which categories it belongs to in facilitating the recognition of entities in geometry. The identification of the geometric entities assists us in identifying the features of the 3D object. The generated features from code classification algorithm give the information of machining parameter through the mapping algorithm. The mapping algorithm focuses on the dimension of the machine for the milling process which is the length offset, corner radius and depth. The project comes out with development of a virtual reality of robot arm movements tools using Matlab software. The tools development uses VR tools and SIMULINK tools which embedded in the software. The scope of the project only caters robot arm without interaction with external environment such as conveyor. The project successes to develop a tool to simulate robot arm movement using VR tools.